2017
DOI: 10.1016/j.fgb.2017.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Real-time visualization of immune cell clearance of Aspergillus fumigatus spores and hyphae

Abstract: Invasive aspergillosis (IA) is a disease of the immunocompromised host and generally caused by the opportunistic fungal pathogen Aspergillus fumigatus. While both host and fungal factors contribute to disease severity and outcome, there are fundamental features of IA development including fungal morphological transition from infectious conidia to tissue-penetrating hyphae as well as host defenses rooted in mechanisms of innate phagocyte function. Here we address recent advances in the field and use real-time i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 12 publications
1
24
0
Order By: Relevance
“…Larval zebrafish are transparent and can be non-invasively imaged and therefore allow for visualization of innate immune cell behavior and fungal development in a live, intact host throughout a multi-day infection. While murine models require enormous fungal inoculums (~10 7 conidia) and host immunosuppression in order to directly visualize immune cell-pathogen encounters within the context of host tissue, the larval zebrafish allows for visualization of smaller doses (10–100 conidia) in wild-type hosts [ 22 ]. Aspergillus infection models in zebrafish have already been developed by our lab and others and recapitulate many aspects of human and mouse infection, including initial phagocytosis of conidia by macrophages and post-germination neutrophil recruitment [ 21 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Larval zebrafish are transparent and can be non-invasively imaged and therefore allow for visualization of innate immune cell behavior and fungal development in a live, intact host throughout a multi-day infection. While murine models require enormous fungal inoculums (~10 7 conidia) and host immunosuppression in order to directly visualize immune cell-pathogen encounters within the context of host tissue, the larval zebrafish allows for visualization of smaller doses (10–100 conidia) in wild-type hosts [ 22 ]. Aspergillus infection models in zebrafish have already been developed by our lab and others and recapitulate many aspects of human and mouse infection, including initial phagocytosis of conidia by macrophages and post-germination neutrophil recruitment [ 21 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, neutrophils are important cells to defense against various pathogens including Aspergillus in the lung (41). The ability of neutrophils to efficiently kill A. fumigatus hyphae in vivo has been demonstrated by the realtime visualization in the zebrafish (42). These results suggested that macrophages and heterophils are required for A. fumigatus infection in chickens.…”
Section: Discussionmentioning
confidence: 89%
“…Similarly, another group found that macrophages cannot always control A. fumigatus growth, and observed lateral transfer of spores to other macrophages [38]. After germination, hyphae can be targeted by both neutrophils and macrophages, and direct contact-mediated killing by neutrophils and macrophages has been observed in larvae [27,41]. In fact, irf8 −/− larvae infected with a fast-germinating strain of A. fumigatus exhibit less death and more fungal clearance compared to wild-type controls, underlining the ability of neutrophils to attack A. fumigatus post-germination [31].…”
Section: Phagocyte Function and Interactions With Fungal Pathogensmentioning
confidence: 99%
“…Injection into the HBV is relatively easy, allowing for high-throughput survival analysis. Furthermore, this location is ideal for visualizing and quantifying phagocyte recruitment as the HBV is typically devoid of macrophages and neutrophils but these cells can easily migrate into the site This ability to image fungal–phagocyte interactions is a major strength of the HBV injection site as the HBV is separated from the environment only by a thin epithelial layer [28,41]. However, as the larva develops, the volume of this space decreases and injection and imaging becomes more difficult.…”
Section: Unique Aspects Of the Zebrafish Toolbox: Infection Localimentioning
confidence: 99%